[OP.5B.05] CHARACTERISATION OF LONGITUDINAL CHANGES IN VASCULAR STRUCTURE AND FUNCTION OVER A 4 YEAR FOLLOW-UP PERIOD: AS ASSESSED BY MRI. (September 2016) - Cecelja, M.; Hussain, T.; Vieira, M. Silva; Phinikaridou, A.; Greil, G.; Spector, T.; Chowienczyk, P.
Abstract : Objective: Vascular aging is characterised by structural changes: wall thickening and change in lumen diameter, together with functional changes in aortic stiffness. We investigated the longitudinal structural and functional changes that occur in the aortic wall over a 4 year follow-up period. Design and method: Magnetic resonance imaging (MRI) was performed in 38 asymptomatic women aged between 53–73 years at baseline and 4 years later over from the aortic arch to aortic bifurcation. Phase-contrast MRI was performed at 2 levels to calculate aortic PWV. Aortic wall diameter and wall thickness were measured using a black-blood MRI sequence. Young's incremental elastic modulus (E) was calculated from the simplified Moens-Korteweg equation: PWV = sqrt(Eh/D), where h is the average aortic wall thickness and D is average aortic diameter. Results: PWV did not differ significantly over the four year follow-up period (mean ± standard deviation for aortic PWV at visit one and two 7.74 ± 1.7 and 7.70 ± 1.5 m/sec respectively, P = 0.85). There was a significant increase in aortic wall thickness (0.16 ± 0.02 cm at baseline and 0.24 ± 0.06 cm at follow-up, P < 0.0001) and decrease in lumen diameter (2.23 ± 0.24 cm at baseline and 1.97 ± 0.14 cm at follow-up, P < 0.0001)). The calculated elastic modulus significantly decreased at follow-up (E at visit one and two 8.68 ± 4.2 and 5.41 ± 2.7 106 dynes/cm2, respectively, P < 0.0001). The dissociation between PWV and calculated E was explained by an increase in wall thickness/diameter ratio over the follow-up period (wall thickness/diameter ratio at visit one and two 0.07 ± 0.01 and 0.12 ± 0.03 respectively, P < 0.0001). Conclusions: In our cohort of older women, increase in aortic wall thickness was the most marked structural change and could potentially offset an increase in PWV produced by intrinsic stiffening of the aortic wall.